Biomechanics of the Hammer Throw: Narrative Review - Castaldi, Gian Mario; Borzuola, Riccardo; Camomilla, Valentina; Bergamini, Elena; Vannozzi, Giuseppe; Macaluso, Andrea (Frontiers in Sports and Active Living, 2022)
Hammer throw is a discipline characterised by unique biomechanical features, which have often captured the interest of scientists and coaches in athletics. However, most studies have been published on technical journals for coaches and there are only few works on the biomechanical aspects of hammer throw in scientific literature. This narrative review provides a critical evaluation of the articles published in scientific and the most relevant technical journals with a particular focus on the biomechanical aspects that underlie the throwing technique and contribute to performance enhancement. The modern throwing technique has many elements in common with that used by the best throwers in the Eighties, underlying a limited development in the biomechanical understanding of throwing motion in recent years. This review analyses the ballistic and environmental aspects of the discipline as well as the motion of the centre of mass of both the hammer and thrower. Furthermore, the orbital movement of the hammer and the forces involved in the throw are evaluated. This review emphasizes the kinematic and dynamic parameters that emerge as the most relevant to improve the throwing performance. Among these, linear release velocity appears to be a fundamental element. To maximise this variable, the athlete is required to accelerate the hammer by applying force. The curve of the time-tangential velocity of the hammer follows a trajectory very similar to that of the forces applied to the hammer-thrower system indicating a strong relationship between the two variables. The thrower uses the action of the leg muscles to gain momentum, which is then transferred to the hammer through the trunk and arm muscles, thus obtaining an increase of the linear release velocity. This review provides coaches with a critical analysis of the hammer throw technique, highlighting relevant factors for future development of training programmes. Our work reveals a substantial gap in the literature, particularly concerning the assessment of preliminary winds, the entry to the first turn and the definition of the rotation axes involved in the throw. A more in-depth analysis of these key elements is required to improve the understanding of the biomechanics of hammer throw.